Twelve new species of Sonerila (Sonerileae, Melastomataceae) from Thailand - Wai, Jarearnsak Sae; Hu, Jer-Ming (Phytotaxa, 2023)
Twelve new species of Sonerila from Thailand are described here: S. anisophylla, S. banthatensis, S. betongensis, S. epiphytica, S. montana, S. peninsularis, S. phuhinrongklaensis, P. phuphanensis, S. reptans, S. subumbellata, S. tenasserimensis and S. tenue. Detailed descriptions, line drawings, color photos, distribution map, ecological data, phenology, DNA barcode sequences, vernacular names and conservation assessment are also provided. Although most of them are narrowly distributed and known only from Thailand, some species might be also found in neighboring countries. Conservation assessments are suggested for all new species, from which seven are assessed as Endangered (EN), two Vulnerable (VU) and three Data Deficient (DD). With the addition of the new taxa, there are now a total of 29 species of Sonerila known from Thailand.